The Relationship Between Gadget Usage Habits, Parenting Stayles And Eating Patterns Of Children Aged 4-7 Years With The Nutritional Status - Imam Syahputra Yamin; Febrina Sulistiawati; May Hardianti (PROFESSIONAL HEALTH JOURNAL, 2025)
Introduction: The rapid advancement in technology and information has significantly transformed the field of communication technology. Today, many parents intentionally give gadgets to their children, believing that these devices can serve as a distraction to keep children calm while they are at work, and to make them feel comfortable at home. However, when gadget usage is uncontrolled and used merely as a distraction tool, it may impact children's behavior and nutritional status. Objectives: This study aims to explore the effects of gadget usage habits, parenting styles, and dietary patterns on the nutritional status of children aged 4-7 years. Methods: This research uses a descriptive observational design with a cross-sectional approach. The study population includes children aged 4-7 years who use gadgets, with a total sample size of 55 children. Data analysis was carried out using the Chi-Square Test. Results: The findings show a significant influence of the three variables—gadget usage, dietary patterns, and parenting style—on the nutritional status of children, with a p-value of 0.00, which is less than 0.05. It can be concluded that gadget usage, parenting style, and dietary patterns significantly affect the nutritional status of children aged 4-7 years. Conclusions: There is a noticeable impact of gadget usage habits, parenting styles, and dietary patterns on the nutritional status of children aged 4-7 years.